Finance and Development, September 1987. (Finance and Development; Finance and Development, 1987)
The enhancement of the IMF's structural adjustment facility is discussed. In its April 1987 meeting, the IMF's Interim Committee highlighted the plight of low-income countries, and outlined a strategy for their recovery. It emphasized that it is crucial for these countries to implement reforms that to be fully effective, will need to be accompanied by the timely provision of additional financing on appropriate concessional terms to support these reforms. The Committee also called upon creditor governments to grant exceptional relief with respect to official credits in highly indebted low-income countries.